PENDEKATAN KEKAR UNTUK MODEL BERSAMA (JOINT MODEL) ATAS DASAR SEBARAN t (A Robust Approach for Joint Model Based on t Distribution) - _ Indahwati; _ Aunuddin; Khairil Anwar Notodiputro; I Gusti Putu Purnaba (FORUM STATISTIKA DAN KOMPUTASI, 2012)
Existing methods for joint modeling are usually based on normality assumption of random effects and intra subject errors. We propose a joint model based on t distribution of the intra subject errors  to improve robustness of the estimation. Our model consists of two submodels: a mixed linear mixed effects model for the longitudinal data, and a generalized linear model for continuous/binary primary response. The proposed method is evaluated by means of simulation studies as well as application to HIV data. Keywords:  joint modeling, longitudinal data, robust, t distribution